PENGEMBANGAN MODUL AJAR PEMBELAJARAN MATEMATIKA BERDIFERENSIASI BERBASIS KHAN ACADEMY KIDS BERMUATAN TPACK UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA FASE A SD - Sugiarto; Sukamto; Mudzanatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the lack of teaching materials that integrate technology into learning. This study aims to develop and test the validity, practicality and effectiveness of a differentiated Mathematics learning module based on Khan Academy Kids containing TPACK to improve the mathematical reasoning skills of Phase A elementary school students. This study uses the Research and Development (R&D) method with the ADDIE research model consisting of five stages, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The subjects of the study were 25 students in grade I of SDN Sampangan 01 Semarang. Data collection instruments included expert validation sheets, teacher response questionnaires on the practicality of the teaching module, and pretest and posttest mathematical reasoning ability tests to measure effectiveness. The results of the study showed that: (1) The developed teaching module was declared valid based on expert assessments with an average score of 99.3% or in the very valid category. (2) The teaching module is declared practical to use based on the acquisition of a score of 75% or is included in the practical category. (3) The effectiveness of the teaching module through the Paired Sample T-Test shows a Sig. (2-tailed) value of 0.000, which indicates an increase in students' mathematical reasoning abilities before and after the learning process is carried out. The SPSS output data from the summary of descriptive statistics shows that the average pretest score is 10.1600 and the average posttest is 11.7600. The N-Gain value obtained is 0.3725. This shows that the development of a differentiated Mathematics learning module based on Khan Academy Kids containing TPACK is effective in improving the mathematical reasoning abilities of elementary school phase A students.